2020
DOI: 10.3390/polym12030590
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Decellularized Amniotic Membrane: Extracellular Matrix as Scaffold for Mammalian Skin

Abstract: Decellularized membranes (DM) were obtained from bovine amniotic membranes (BAM) using four different decellularization protocols, based on physical, chemical, and mechanical treatment. The new material was used as a biological scaffold for in vitro skin cell culture. The DM were characterized using hematoxylin-eosin assay, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR-ATR), and differential scanning calorimetry (DSC). The in vitro cytotoxicity of DM was evaluated using MTT.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 85 publications
(82 reference statements)
0
13
0
2
Order By: Relevance
“…After 600°C, the inorganic constituents in the dSCM might be thermally degraded (Galia et al, 2011). On the other hand, the DSC thermogram illustrated the typical thermal denaturation peak of collagen (50°C) (Figure S1b) (Ballesteros et al, 2020;Claudio-Rizo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…After 600°C, the inorganic constituents in the dSCM might be thermally degraded (Galia et al, 2011). On the other hand, the DSC thermogram illustrated the typical thermal denaturation peak of collagen (50°C) (Figure S1b) (Ballesteros et al, 2020;Claudio-Rizo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Residual dsDNA could be directly linked to the remaining cells and trigger unfavorable host reactions. Quantitative assays have shown that less than 50 ng dsDNA per mg ECM dry weight is enough to achieve decellularization [ 57 , 58 ].…”
Section: Preparation and Identification Of Decm-derived Bioinksmentioning
confidence: 99%
“…The organs from which dECM have been harvested range from skin, lung, cornea, , bladder, kidney, placenta, , amniotic membrane, cartilage, adipose tissue, , esophagus, and liver and have been used in organ regeneration and in vitro model construction. Comercially available human decellularized dermal matrix (Glyaderm) was shown to enhance re-epithelialization and healed full thickness skin defects when seeded with adipose derived stem cells (ASC) in murine wound models .…”
Section: Hydrogel As Bm Mimicsmentioning
confidence: 99%